HUBUNGAN POSTUR KERJA DENGAN KELUHAN KELELAHAN KERJA PADA OPERATOR CONTAINER CRANE PT. TERMINAL PETI KEMAS SEMARANG - Nurrina Riska Amalia; Ida Wahyuni; Ekawati Ekawati (Jurnal Kesehatan Masyarakat (Undip), 2017)
In the development of the logistics rapid growth, removal and transporting goods indispensible the existence of a conveyance forklift, the container crane for example. It’s operated by an operator with a seated position and bent over four hours in static position, and very risky to face the fatigue complaints so as to be attracting many sides. This research was aimed to recognized the relationship between working posture with working fatigue on container crane operator. The research was qualitative research with cross sectional research design. The subject in this research was all container crane operator which totaled 42 people. The data analysis used Chi-square with alternate Fisher’s Exact Test with 95 % of significance level. The measurement of working posture used RULA method while the working fatigue measurement used Alat Ukur Perasaan Kelelahan Kerja questionnaire (KAUPK2). The results showed that there was a relationship between working posture (p = 0,0001) with working fatigue complaint in container crane operator, there was no relationship between the age (p = 0,188) and tenure (p = 0,225) with the working fatigue complaint. It was suggested to the company to rejuvenate the old container crane with the new which was more ergonomic so as to be reduce the number of working fatigue complaint.